Tratamento anaeróbico dos efluentes oriundos da bovinocultura de leite em biodigestor tubular - Mendonça, Elisabete Ferro (2009)
The wastewater resulting from milk production processes with animals at free stall barns has huge organic matter concentration and requires treatment before being disposed at the environment. At this study, the dairy cattle wastewater from free stall barns was treated in horizontal tubular anaerobic reactors with continuous flow and 9.6 liters volume each, made with polyvinyl chloride (PVC). The material was collected at Iguaçu Farm, with geographic coordinates latitude 25°02'43.07" south, longitude 53°46'51.85" west and 641 meters altitude, sieved at 2 mm mesh and stored at -18 °C, conditioned in polyethylene terephthalate (PET) packs. The material was put in room temperature before being added to the reactor each day. Different loads were used, resulting in retention times equals to were 8, 10, 15 and 20 days. Two temperatures were used: 30 and 35 °C; with 4 replications. Statistical data were evaluated by factorial crossover design 4 x 2 x 4, 4 factors of hydraulic retention time (HRT), 2 temperature factors and 4 replicates, with the average calculated by the Tukey method. They were evaluated the chemical oxygen demand (COD) removal, by colorimetric method, total solids (TS) and volatile solids (VS), by gravimetric methods. The best treatments were met with 20 days HRT and 30 °C, with average 83.30% 76.16% and 86.23% of COD, TS and VS removed. The biogas production was measured relatively to COD, TS and VS removals, resulting in 1.32 m³ of biogas kg-¹ DQO at 5 days of HRT and 35 ° C. At the 8 days HRT and 30 ° C, they resulted in 1.05 and 1.01 m³ of biogas · kg-¹ of TS and VS removed from the system, respectively.